(untitled) (Conference Zone, 2022)
Data on 47 patients with stage Tis-2cN0M0 breast cancer who underwent surgical treatment with sentinel lymph node biopsy were included. All patients underwent preoperative ultrasound of the regional lymph nodes, followed by the introduction of a radiopharmaceutical (RP) and lymphoscintigraphy of the regional zones of the lymphatic outflow. A retrospective evaluation of the results of visualization of sentinel lymph nodes was performed according to the data of the clinical (ultrasound, lymphoscintigraphy) and intraoperative (GammaFinder) diagnostic methods used. The accuracy of the ultrasonic research method was 76.5%, of the radionuclide - 87.2%. The frequency of false-negative results of an urgent histological conclusion did not exceed 3%. The percentage of finding the sentinel lymph node intraoperatively was 70.2%. With the introduction of radiopharmaceuticals on the eve of surgery and with radiopharmaceutical activity above 180 MBq, the probability of intraoperative detection of the sentinel lymph node is higher. In 51% of patients, lymphorrhea ceased on the 57th day after the operation.